Acoustic and thermal performances of ceramic tiles and tiling systems. Issue 6 (July 2015) - Rambaldi, E.; Prete, F.; Bignozzi, M.C.
Abstract: Acoustic and thermal performances of floating floor and/or radiant floor can be improved by using ceramic tiles with tailored porosity and microstructure. Porcelain stonewares are still the most widespread typology of tiles, due to their high physical and mechanical performances coming from a very low level of open porosity and water absorption (≤0.5 wt%). However their closed porosity values, usually neglected, can be significantly different from one product to another. As a consequence, the properties directly dependent on the total porosity, such as thermal and acoustic ones, may be strongly diverse among commercial tiles. Several commercial porcelain stoneware tiles having different composition, microstructure and porosity, were selected for the present work. These tiles, alone or coupled with different types of resilient underlayer materials (glass fibre, cork and rubber), were studied on the basis of dynamic stiffness. Their acoustic and thermal properties were investigated in terms of thermal conductivity and walking noise reduction.